Highlighting the Links between Islamic Accounting and the Cash Waqf - Saidu, Oluwaseun Sulaiman (International Journal of Islamic Business and Economics (IJIBEC), 2019)
The paper explores and ultimately highlights the link between the two concepts via a diachronic approach, tracing the Islamic institution of the cash Waqf and its book keeping activities thereby garnering sufficient evidence to conclude that the Islamic Accounting is in fact an old concept as it has been used in the accounting for Cash Waqf in the Ottoman times and in relatively recent times. Implication wise, understanding the accountability rudiments relative to Islamic institutions would go a long way in bolstering these institutions and ensuring their survival intergenerationally.